Every Little Helps? ESG News and Stock Market Reaction - Capelle-Blancard, Gunther (Journal of business ethics, 2019)
Stories about corporate social responsibility have become very frequent over the past decade, and managers can no longer ignore their impact on firm value. In this paper, we investigate the extent and the determinants of the stock market’s reaction following ordinary news related to environmental, social and governance issues—the so-called ESG factors. To that purpose, we use an original database provided by Covalence EthicalQuote. Our empirical analysis is based on about 33,000 ESG news (positive or negative), targeting one hundred listed companies over the period 2002–2010. On average, firms facing negative events experience a drop in their market value of 0.1%, whereas companies gain nothing on average from positive announcements. We find also that market participants are responsive to the media, but they do not react to firms’ press releases or to NGOs’ disclosures. Moreover, our results indicate that sector’s reputation mitigates the loss (the goodwill hypothesis) and that cultural proximity and lexical contents of ESG disclosures play a significant role in the magnitude of the impact.